(untitled) (Journal of the College of Education for Women, 2024)
This research aims to present and analyze trends in industrial efficiency of endemic activities within the governorates of the study area, and then to analyze general industrial efficiency and its role in achieving development by adopting many quantitative statistical methods that researchers and scholars can use to measure the efficiency of industrial activities within spatial space. There is also more than one indicator that can be used in order to apply these measures on the ground, the most important of which is ((the number of workers, wages and salaries, the value of production and the value of supplies in addition to the value added)) which we will adopt in the research. The results are drawn by answering the research problem represented by the varying level of efficiency of the industrial sector in the provinces of Maysan and Dhi Qar, in addition to the fact that efficiency does not reflect the reality of the industries endemic therein. The research reached a set of conclusions; the industrial efficiency of the industrial sector in the two governorates of the study area is concentrated within specific industrial branches, mainly represented by the petroleum products industry, the semi-metallic minerals industry, and the food products industries, , which made it at the forefront of industrial activities in terms of efficiency at the level of manufacturing industries in the study area, which enhanced its ability to contribute to achieving economic development and social development alike in the structure of the manufacturing sector. in contrast to the weakness or lack of importance of other industrial branches